Bunker procurement strategies of liner companies part I operational strategies to reduce bunker cost - Tay, Bing Fa. (2011)
Bunker is an indispensable form of energy for powering vessels to stimulate world trade. However, there are several problems arising out of bunker procurement. Shipping markets inherently carry high risks, but the volatility of bunker prices adds further uncertainty for ship operators. Besides, as bunker costs constitute a significant portion of the voyage costs, high bunker prices may threaten the profitability of any company. Lastly, stringent regulations have been drawn up by global bodies and the International Maritime Organization (IMO) to control vessel emissions, which have increased over the years. As a result, careful selection of bunker grades is necessary when entering various regions where emissions are strictly controlled. Container line shipping serves a global market with large fleets that consume a tremendous amount of bunker. Hence, bunker procurement is an important tool to ensure compliance with international regulations while keeping healthy profit margins through reduction of bunker costs. The project aims to suggest a set of bunker procurement strategy for liner companies to deal with the problems mentioned above. Hence, the strategy was divided into 3 aspects – Operational measures to reduce bunker costs; financial measures to cope with the risk of fluctuating bunker prices; and lastly environmental measures to ensure compliance with international regulations.